2014
DOI: 10.14434/josotl.v14i3.5033
|View full text |Cite
|
Sign up to set email alerts
|

Finding Your “Spanish Voice” Through Popular Media: Improving Students’ Confidence and Fluency

Abstract: This article shares an innovative course design that incorporates cultural connections and comparisons, interpersonal communication, and a relaxing classroom environment to facilitate learning and language development. By using authentic texts as the medium for learning, it provides a case example of an upper-division curriculum that focused on cognitive skills, elicited conversational dialogues, exposed and promoted the use of different registers, and tapped students’ existing schema around stimulating topics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Although the findings are in many ways specific to teaching deviance in a sociology course, we believe that the strengths from this project could be adapted in other courses and disciplines and with varying course sizes. First, the use of popular media served us well to connect with the students and get them thinking beyond the classroom or textbook, consistent with other findings from other disciplines including world languages and nursing (Hyde and Fife 2005; Maseda and DeFeo 2014). Through discussions, we found that students were interested and engaged in the discussion of the show The Handmaid’s Tale .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Although the findings are in many ways specific to teaching deviance in a sociology course, we believe that the strengths from this project could be adapted in other courses and disciplines and with varying course sizes. First, the use of popular media served us well to connect with the students and get them thinking beyond the classroom or textbook, consistent with other findings from other disciplines including world languages and nursing (Hyde and Fife 2005; Maseda and DeFeo 2014). Through discussions, we found that students were interested and engaged in the discussion of the show The Handmaid’s Tale .…”
Section: Discussionsupporting
confidence: 79%
“…Prior research suggests that incorporating relevant media into courses across disciplines has beneficial impacts on student learning and engagement (Belet 2017; Maseda and DeFeo 2014). For example, incorporating YouTube examples of Durkheim’s concepts, such as explaining mechanical solidarity using American soccer fan culture, versus verbally giving the example equalized outcomes between disadvantaged and advantaged students (Belet 2017).…”
Section: Personal Reflexive Statementmentioning
confidence: 99%
See 1 more Smart Citation